A simulation study on model predictive control for building automation - Yeo, Wei Jie (Nanyang Technological University, 2020)
Air Conditioning and Mechanical Ventilation (ACMV) systems are found in almost all buildings and are responsible for a huge portion of the energy expenditure. The energy usage of ACMV systems are monitored inside the Building Management System (BMS). The conventional control system being used in the current times include: PID controllers, On/Off controllers and If/Else controllers, the building model utilizing these controllers are referred to as the baseline model in this study. The focus of this study is on a different kind of control system called Model Predictive Control (MPC). This study aims to investigate the benefits of using MPC compared to conventional controllers, particularly the PID controller, such benefits include not only energy savings but also increased thermal comfort. The simulation study will be done by using different software which includes: Sketchup, Openstudio, Energyplus, Matlab and BCVTB. A baseline model and MPC model will be created and simulated to generate a detailed report on the building performance. The comparison will be focused on the energy consumption and thermal comfort levels.